Financial Management in Online Fashion MSMEs in Bandung City to Improve Business Efficiency and Sustainability (Case Study at Dlusia Dress) - Narimawati, Umi; Syafei, M. Yani Syafei; Febriansyah, Angky; Tribuana , Dhimas (EQUATOR SINAR AKADEMIA, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy, yet many face challenges in financial management, including Dlusia Dress, a fashion sector MSME. This community engagement program aims to enhance the financial management capabilities of Dlusia Dress, focusing on cost of goods sold (COGS) calculation and business budgeting. Conducted over six months, from April to October 2024, the program consisted of three stages: a preliminary survey, training and mentoring sessions, and an evaluation phase. The results demonstrate significant improvements in financial management practices. Dlusia Dress successfully separated personal and business finances, implemented accurate COGS calculations, and developed a structured business budget. Additionally, the business owner adopted systematic transaction recording, enabling real-time cash flow monitoring. The final evaluation revealed increased financial awareness and skills, providing a strong foundation for long-term business sustainability. In conclusion, targeted and needs-based interventions can help MSMEs address financial management challenges, improve operational efficiency, and enhance competitiveness. These findings highlight the importance of integrated approaches in supporting MSMEs toward achieving sustainable growth and resilience.